A práxis hermenêutica como responsabilidade ética - Testa, Edimarcio (Universidade do Vale do Rio dos Sinos, 2022)
Here, I argue that hermeneutic praxis is a responsible activity. The theme of responsibility is present in the hermeneutic reflections of Hans-George Gadamer, but in an unsystematic way. It is still the object of reflection on the part of some interpreters who, with the exception of Theodore George (2020), do not develop it enough. Both systematization and the broader development of ethical responsibility, in the activity of understanding and interpreting, help in their own understanding and lay the foundations for reflection on current practical problems that require, above all, the consideration of otherness, whether on a personal, social, political, cultural, or ecological level. In the context of Gadamer's hermeneutic thought, the interpreter's activity is defined as praxis, since his model is the Aristotelian phronesis of Nicomaqueia Ethics. After the establishment of the hermeneutic meaning of phronesis, compared to the Aristotelian meaning, I characterize hermeneutic praxis, based on its fundamental constitutive elements, as a mediating activity of the universal in the private sphere, guided by ethical knowledge, rooted in ethical life and in the dialogical process. I conclude by presenting five forms of responsibility that focus, respectively, on "choice", "response", "self-responsibility", "singularity" and "understanding" itself. I argue that, despite their peculiarities, these forms are based on the practical exercise of hermeneutics and are thus, permeated by it. With this, I take the assumption that they merge into the generality of the notion of hermeneutic praxis, as well as in the encounter with otherness, which gives them fundamentally an ethical character.
Keywords: Gadamer; Hermenêutica filosófica; Phronesis; Práxis hermenêutica; Responsabilidade ética; Philosophical hermeneutics; Hermeneutic práxis; Ethical responsibility; ACCNPQ::Ciências Humanas::Filosofia